THE EFFECT OF WORK ASSESSMENT AND WORKLOAD ON JOB SATISFACTION AND ITS IMPACT ON EMPLOYEE PERFORMANCE - Mufida, Amalina; Sawitri, Dyah; Santoso, Nugroho Agus (Politeknik Negeri Ambon, 2025)
Introduction: This study aimed to determine the influence of performance assessment and workload on job satisfaction, which has an impact on employee performance at the Mojokerto Regency DPRD secretariat office.Methods: This research uses a quantitative approach. The population of this study consists of 52 employees working at the Mojokerto Regency DPRD Secretariat office. Research that uses all members of the population is called a total sample or census. This study employs a research instrument in the form of a questionnaire. The respondents’ answers are then tabulated and processed using the Warp PLS Version 6 program.Results: Research findings indicate that the impact of work assessment on employee satisfaction has not been proven to be significant. This is due to employee dissatisfaction with their performance assessment. It has been proven that workload has a significant impact on employee satisfaction; this means that effectively managing the existing workload can have a positive impact on increasing employee job satisfaction. It is not proven that work assessment has a significant effect on performance. This demonstrates that performance assessment is subjective. It is proven that workload has a significant impact on performance. It has been proven that the higher the workload assigned, the greater the employee’s performance will increase. It is proven that employee satisfaction has a significant effect on performance; this is proven by the fact that employee performance provides satisfaction for the employees themselves. It is proven that work assessment has an impact on performance through job satisfaction. It has been proven that workload has an impact on performance, as measured by job satisfaction, at the Mojokerto Regency DPRD Secretariat Office. Keywords: Performance Appraisal, Workload, Job Satisfaction, Employee Performance